B-107 Distinct mechanisms of hormonal control of HIV latency in T-cells and microglial cells. (January 2016) - Karn, Jonathan; Das, Biswajit; Dobrowolski, Curtis; Garcia-Mesa, Yoelvis; Alvarez-Carbonell, David; Milne, Stephanie; Scully, Eileen; Deeks, Steven; Gandhi, Monica; Johnston, Rowena
Abstract : Unbiased shRNA library screens identified novel genes and pathways that are required to maintain HIV latency in both T-cells and microglial cells. In T-cells, one of the most prominent and robust "hits" was the estrogen receptor type 1 (ESR-1). Specific antagonists of ESR-1, such as Tamoxifen and Fulvestrant, are weak proviral activators but sensitize latently infected cells to very low doses of the proviral activators TNF-α (NF-κB inducer) and SAHA (HDAC inhibitor). The ESR-1 agonists, propylpyrazoletriol (PPT) diethylstilbestrol, and estrogen had the opposite effect and strongly suppressed both TNF-α and SAHA reactivation. In the HAART treated patient samples there was a modest increase of spliced HIV mRNA when resting memory cells were treated with the ESR antagonists Fulvestrant or Tamoxifen alone. Syngeristic reactivation was observed by combining ESR antagonists and HDACi. β-Estradiol at concentrations in the physiological range led to dramatic reductions in proviral reactivation efficiencies, especially in women, pointing to gender-specific differences in the control of HIV latency. Thus, ESR-1 is a pharmacologically attractive target that can be exploited in the design of therapeutic strategies aimed at inducing proviral clearance from T-cells to eradicate the latent reservoir. In microglial cells ESR-1 does not play a major role in controlling HIV latency, but retinoid X receptor (RXR) plays an analogous role. Treatment of microglial cells with the RXR antagonist Bexarotene blocks HIV transcription and can lead to long-term suppression of proviral reactivation. Thus, our results point to cell type-specific differences in HIV transcriptional control that can be exploited as part of design of Cure strategies.